Japan's quest for nuclear energy and the price it paid : accidents, consequences, and lessons learned for the global nuclear industry - Behling, Noriko Hikosaka; Behling, Thomas G.; Williams, Mark C.; Managi, Shunsuke (Elsevier, 2019)
Japan's Quest for Nuclear Energy and the Price it has Paid: Accidents, Consequences, and Lessons Learned for the Global Nuclear Industry identifies major accidents in Japan that have happened at different stages of the nuclear fuel cycle in Japan, assesses the underlying causes of nuclear accidents, and identifies other systemic problems in the nuclear industry. It provides recommendations on how government, industry and academic institutions can work together toward achieving a zero-accident safety culture.